Leading Indicators of Real Activity and Inflation for Turkey, 2001-2010 - Sumru Altug; Erhan Uluceviz (Koç University-TÜSİAD Economic Research Forum (ERF), 2011)
This paper develops a set of leading indicators of industrial production growth and consumer price inflation for the period 2001-2010. The choice of indicators is based on pseudo out-of-sample forecasting exercise implemented by Stock and Watson (2003), amongst others. We find that asset prices that reflect expectational factors or interest rates that capture the costs of borrowing for the Turkish economy tend to have the greatest predictive power for future real activity and inflation. Our findings provide evidence on the factors determining real activity and inflation in a period of disinflation and normalization for the Turkish economy.
Keywords: E1; E32; E37; E58; F43; O52; 330; Real activity; inflation; leading indicators; out-of-sample forecasting; combination forecasts; inflation targeting; Turkey; Inflationsrate; Industrieproduktion; Verbraucherpreisindex; Prognoseverfahren; Inflationssteuerung; Türkei